Students' Engagement in Learning Listening Skills through Plotagon Story - Nurjihan Najwa Fitriyah; Adib Ahmada (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
This study investigates students' engagement in learning listening skills through the use of Plotagon Story in an EFL context. While previous studies have primarily focused on learning outcomes and speaking skills, this research examines engagement as a multidimensional process consisting of behavioral, emotional, and cognitive dimensions. A descriptive qualitative case study design was employed, involving 20 junior high school students and one English tutor at the ASYEE Basic Course Club in Banyuwangi. Data were collected through classroom observations and semi-structured interviews with both students and the tutor, and analyzed using thematic analysis. The findings indicate that the use of Plotagon Story contributes to increased student engagement, particularly in terms of active participation, positive emotional responses, and the use of cognitive strategies such as contextual inference and selective attention. However, the results also reveal variations in engagement levels, including instances of distraction and cognitive difficulty, suggesting that the effectiveness of multimodal learning depends on task design and learner characteristics. This study highlights that engagement in digital learning environments is dynamic and context-dependent rather than uniformly positive. It also extends the use of animation-based storytelling from speaking to listening contexts. The findings suggest that educators should carefully integrate multimedia tools to balance engagement and comprehension. Future research is recommended to explore long-term effects and broader educational settings.